Implementation of Internal Control in the Accounting Information System of Credit and Cash Sales at PT Wings Surya in Surabaya: Penerapan Pengendalian Intern Pada Sistem Informasi Akuntansi Penjualan Kredit dan Tunai Pada PT Wings Surya di Surabaya - Laila Rahayu Lestari; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
In the current industrial era, there is a lot of emerging competition in technology and information. The increase in information causes the growth of technology to be faster. This study aims to determine whether the application of internal control accounting information systems for credit and cash sales at PT Wings Surya in Surabaya is in accordance with the theory. This research method uses descriptive method. The data collection used were interviews, observations, documentation, and literature studies. The credit and cash sales accounting information system implemented at PT Wings Surya has used a computerized system well. Namely by using the SmartOpr system and SAP System. The results of the study show that the internal control of the credit and cash sales accounting information system at PT Wings Surya in Surabaya is in practice in accordance with existing theory.